2011
DOI: 10.1186/1744-9081-7-44
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical processing of speech regularities underlies reading and music aptitude in children

Abstract: BackgroundNeural sensitivity to acoustic regularities supports fundamental human behaviors such as hearing in noise and reading. Although the failure to encode acoustic regularities in ongoing speech has been associated with language and literacy deficits, how auditory expertise, such as the expertise that is associated with musical skill, relates to the brainstem processing of speech regularities is unknown. An association between musical skill and neural sensitivity to acoustic regularities would not be surp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
122
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(139 citation statements)
references
References 89 publications
15
122
1
Order By: Relevance
“…Indeed, participants with higher Rhythm Sequence Factor scores were more proficient on a number of language and cognitive measures, including auditory working memory, word reading, and non-word reading. This finding replicates reports of a link between rhythm sequence perception and both reading (Atterbury, 1985;McGivern et al, 1991;Douglas & Willatts, 1994;Overy, 2000Overy, , 2003Forgeard et al, 2008;Dellatolas et al, 2009;Strait et al, 2011;González-Trujillo et al, 2012;Flaugnacco et al, 2014) and verbal memory (Saito, 2001). Further research (longitudinal and cross-sectional) is needed to understand how links between rhythm and language skills change with age.…”
Section: Language Correlates Of Rhythm Skillsupporting
confidence: 78%
See 1 more Smart Citation
“…Indeed, participants with higher Rhythm Sequence Factor scores were more proficient on a number of language and cognitive measures, including auditory working memory, word reading, and non-word reading. This finding replicates reports of a link between rhythm sequence perception and both reading (Atterbury, 1985;McGivern et al, 1991;Douglas & Willatts, 1994;Overy, 2000Overy, , 2003Forgeard et al, 2008;Dellatolas et al, 2009;Strait et al, 2011;González-Trujillo et al, 2012;Flaugnacco et al, 2014) and verbal memory (Saito, 2001). Further research (longitudinal and cross-sectional) is needed to understand how links between rhythm and language skills change with age.…”
Section: Language Correlates Of Rhythm Skillsupporting
confidence: 78%
“…Mounting evidence suggests that rhythmic deficits are tied to language impairment: abnormally poor reading and phonological awareness have been linked to difficulties with rhythm skills as diverse as synchronization (Thomson, Fryer, Maltby, & Goswami, 2006; Thomson & Goswami, 2008;Corriveau & Goswami, 2009;Tierney & Kraus, 2013b;Flaugnacco et al, 2014), beat extraction (David, Wade-Wolley, Kirby, & Smithrim, 2007), metrical perception (Huss, Verney, Fosker, Mead, & Goswami, 2011), rhythm memory (Dellatolas, Watier, Le Normand, Lubart, & Chevrie-Muller 2009;González-Trujillo, Defior, & Gutiérrez-Palma, 2012;Flaugnacco et al 2014), and rhythm discrimination (McGivern, Berka, Languis, & Chapman, 1991;Douglas & Willatts, 1994;Strait, Hornickel, & Kraus, 2011). In fact, links between synchronization ability and reading readiness skills have even been observed in pre-schoolers too young to have received reading instruction (Woodruff Carr, White-Schwoch, Tierney, Strait, & Kraus, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…They found that repetition enhanced stimulus representation (subcortical auditory event-related potential, ERP, responses), but that this repetition effect was weakened in dyslexia. Similar results were found for poor readers (Strait, Hornickel, & Kraus, 2011). Oganian and Ahissar (2012) also measured the impact of repetition on reading rate and found that for controls, irregular words quickly become "regular" in a repeated context.…”
Section: Learningsupporting
confidence: 72%
“…Herrera et al (2011) demonstrated that 2 years of phonological and music training improve reading readiness in native speakers and L2 learners. Strait, Hornickel, and Kraus (2011) Adult musicians performed better than musically naive subjects and equivalently to Chinese experts in the lexical tone discrimination task…”
Section: Enhanced Phonological Processing and Production And L2 Comprmentioning
confidence: 99%